Detoxified lipooligosaccharide from nontypeable Haemophilus influenzae conjugated to proteins confers protection against otitis media in chinchillas. - Gu, X X (1997)
Detoxified-lipooligosaccharide (dLOS)-protein conjugates from nontypeable Haemophilus influenzae (NTHi) elicited a significant rise of anti-LOS antibodies with bactericidal activity in rabbits (X.-X. Gu, C.-M. Tsai, T. Ueyama, S. J. Barenkamp, J. B. Robbins, and D. J. Lim, Infect. Immun. 64:4047-4053, 1996). In this study, we evaluated whether vaccination with the conjugates would protect against NTHi otitis media in chinchillas. Fifty-eight chinchillas received three subcutaneous or intramuscular injections of dLOS-conjugated tetanus toxoid, dLOS-conjugated high-molecular-weight proteins from NTHi, or saline (control) in Freund's adjuvant and then were challenged by intrabullar inoculation with 140 CFU of NTHi. All vaccinated animals responded with elevated serum titers of anti-LOS antibody, and 49% (19 of 39) demonstrated bactericidal activity against the homologous strain. Otitis media with culture-positive NTHi effusions developed in all 19 controls and 56% (22 of 39) of the vaccinated animals during a period of 21 days (P < 0.001). Bacterial counts of the middle ear effusions were lower in the vaccine groups than in the controls (P < 0.01). The incidences of infection in the unchallenged ear or inner ear were 26 or 28% in the vaccine groups and 53 or 58% in the controls (P < 0.05). The signs of infection observed by otoscopy were less severe in the vaccine groups than in the controls. There was no significant difference between the two vaccine groups. These data indicate that active immunization with LOS-based conjugates reduces the incidence of NTHi-induced otitis media.